The Impacts of Korean Wave on Gusjigang Philosophy in Kudus Regency - Fajrin, Fitrotul; Utomo, Cahyo Budi; Alimi, moh Yasir (Universitas Negeri Semarang, 2023)
The lifestyle development of Kudus City high school students who follow the Korean Wave has raised concerns over the decline of the long-rooted local culture of Gusjigang. This study aimed to determine the Korean Wave lifestyle, explain the influencing factors of the lifestyle, and analyze the impact of the Korean Wave lifestyle on Gusjigang values. A qualitative approach was employed in this study, with phenomenological research as the research design. The data in this study were obtained from the research informants. The data validity checking was conducted with the power credibility test, which in this study adopted the triangulation method. The current trend of the Korean Wave lifestyle among high school students in the Kudus Regency involves constantly seeking information about K-Pop through social media and mixing Korean and Indonesian in their daily conversations, which indicates the acceptance of Korean lifestyle. Several contributing factors to the Korean Wave lifestyle of high school students in Kudus Regency were the music lyrics' connection to the high school students' personal lives. At present, the Gusjigang lifestyle is still adhered to by high school students in Kudus City so that it keeps the habits that have been practiced for years.